High stability of bilayer nano-emulsions fabricated by Tween 20 and specific interfacial peptides. (15th March 2021) - Zhao, Qiyue; Wu, Chao; Yu, Cuiping; Bi, Anqi; Xu, Xianbing; Du, Ming
Graphical abstract: Highlights: A stable bilayer nano-emulsions were prepared with peptides from cod bone. The bilayer nano-emulsions exhibit high stability. The interfacial peptides identified by Nano-LC-Q-TOF-MS. Abstract: To ensure emulsions to be continuously stable, the hydrolysates recovered from cod bones by papain acted as a natural surfactant to synthesize high-stability bilayer nano-emulsions. As assisted by Tween 20, the average diameter of synthesized nano-emulsion with enzymatic hydrolysate could exhibit stability between 300–400 nm under a broad range of pH (4–8), temperatures (30–90 °C) and salt concentration (25–250 mM). With the addition of the hydrolysates, the rate of increase of the TBARS value in the emulsion decreased. Moreover, the bilayer structure of the nano-emulsion was characterized under an atomic force microscopy and a cryo-scanning electron microscopy. Nano-LC-Q-TOF-MS was adopted to primarily identify peptides that contained hydrophobic and hydrophilic amino acids at the emulsion interface. Besides, the absorbed peptides on the interface of emulsion enhanced the stability of emulsion lipid oxidation.